Blood-based biomarkers for detecting Alzheimer's disease pathology in cognitively impaired individuals within specialized care settings : A systematic review and meta-analysis - Pahlke, Sarah; Kahale, Lara A.; Mahinrad, Simin; Sousa-Pinto, Bernardo; Vieira, Rafael José; McAteer, Mary Beth; Claessen, Thomas; Contador, José; Hofmann, Anna; Kuchenbecker, Lindsey A.; Machado, Luiza S.; Warmenhoven, Noëlle ; 0009-0003-0557-5102; et al. (Alzheimer's and Dementia, 2025)
BACKGROUND: This systematic review and meta-analysis aimed to assess the diagnostic test accuracy of blood-based biomarkers (BBMs) for detecting Alzheimer's disease (AD) pathology in cognitively impaired individuals in specialized care settings. The overarching goal is to inform the development of a clinical practice guideline, led by the Alzheimer's Association, for use in clinical practice. METHODS: A systematic search of MEDLINE, Embase, and Cochrane Library was conducted from January 2019 to November 2024. Studies evaluating the diagnostic test accuracy of plasma phosphorylated tau (p-tau) and amyloid beta (Aβ) tests (p-tau217, %p-tau217, p-tau181, p-tau231, and Aβ42/Aβ40) compared to reference standard tests (cerebrospinal fluid [CSF] AD biomarkers, amyloid positron emission tomography [PET], or neuropathology) in individuals with cognitive impairment (mild cognitive impairment or dementia) in specialized care settings were included. Pooled diagnostic test accuracy measures were calculated, including sensitivity, specificity, and likelihood ratios. Across a range of pre-test probabilities, we evaluated how much a positive or a negative test result would lead to a change in the probability of having amyloid positivity (post-test probability). All analyses were conducted for each test within each biomarker. The Quality Assessment of Diagnostic Accuracy Studies 2 tool was used to evaluate the risk of bias, and the certainty of the evidence was assessed using the Grading of Recommendations, Assessment, Development, and Evaluation approach. RESULTS: Across 49 observational studies meeting eligibility criteria, 31 different BBM tests were examined. When evaluated using a single cut-point, the diagnostic test accuracy varied considerably across tests: the pooled sensitivity ranged from 49.3% (95% confidence interval [CI]: 41.2–57.4) to 91.4% (95% CI: 86.6–94.6), and the pooled specificity ranged from 61.5% (95% CI: 45.6–75.3) to 96.7% (95% CI: 87.8–99.2). Differences in post-test probability based on a range of pre-test probabilities varied greatly across tests. Furthermore, the certainty of evidence across tests ranged from moderate to very low. Most included studies were judged to be at high risk of bias, particularly in domains related to patient selection, index test conduct, and reference standard. CONCLUSION: This systematic review provides a comprehensive synthesis of the current evidence on the diagnostic accuracy of BBMs for detecting AD pathology in cognitively impaired individuals in specialized care settings. The findings serve as a foundation for an accompanying clinical practice guideline that provides evidence-based recommendations for BBM use in the clinical diagnostic pathway. Given continuous developments in this rapidly evolving field, ongoing evaluation will be critical to ensure the synthesized evidence and clinical guidelines remain up to date and maintain clinical relevance. Highlights: This is the first comprehensive systematic review and meta-analysis to evaluate the diagnostic accuracy of blood-based biomarker (BBM) tests specifically in individuals with objective cognitive impairment seen in specialized care settings. Across 49 studies, BBM test performance varied widely. Pooled sensitivity ranged from 49.3% to 91.4% and specificity from 61.5% to 96.7%, depending on the analyte and assay platform. This review followed the Cochrane Handbook for Systematic Reviews of Diagnostic Test Accuracy, the Grading of Recommendations, Assessment, Development, and Evaluation approach to assess the certainty of evidence. This review served as the evidence base for the Alzheimer's Association's new clinical practice guidelines on BBMs, providing structured, evidence-based guidance for implementing BBMs in the diagnostic workup of suspected Alzheimer's disease. The review underscores that BBM test performance is assay- and platform specific and advises clinicians and laboratory directors to interpret results in the context of the specific test used and integrate the results with a comprehensive clinical assessment.
Publisher Copyright: © 2025 The Author(s). Alzheimer's & Dementia published by Wiley Periodicals LLC on behalf of Alzheimer's Association.
Keywords: Alzheimer's disease; blood-based biomarkers; cognitive impairment; secondary care; specialty care; systematic review; tertiary care